Pengaruh Aktivasi Bentonit Wonosegoro terhadap Perbaikan Sifat Fisis Minyak Pelumas Bekas Industri - Gogot Haryono (Eksergi, 2008)
Bentonit is a kind of ore which has a high adsorption power due to its hígh content of montmorilonit. Its wìdely used in many applications as well as an activated carbon. In fact, activated bentonit can improve physical properties of used lubrícant oil partially its Rëdwood vìscocity, flash point and carbon residue. In this research, the activation procceses including heating, pressurizing and acíd methods. Such methods were conducted ìn a muffle burner (at temperature of 280, 300, 320, 340, 360 and 38 degree C, ín a pressure vessel (at pressures of 1.75; 2.23; 2.54; 2,66; and 3.02 atm), and three neck bottles (at acid concentrations of 0.1; 0.2; 0.3; 0.4 and 0.5 N), respectìvely. The activated bentonit was thereafter tested to absorp a quantity of sample used lubricant oil. From these experiments, it was concluded that activated bentonit can increase the Redwood viscocity and flash poínt of used lubrícant oil and also decrease its carbon residue. The optimum temperature, pressure and acidconcentratíon obtainedwere 36tC, 2.66 atm and 0.4 N, respectively. At this condition, the used lubricant oil had a Redwood víscocity 125.9 cP, flash point of 112 degree C and carbon residue of 22.05%.